2018
DOI: 10.1101/324558
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phenotype-specific enrichment of Mendelian disorder genes near GWAS regions across 62 complex traits

Abstract: 1Although recent studies provide evidence for a common genetic basis between complex traits 2 and Mendelian disorders, a thorough quantification of their overlap in a phenotype-specific 3 manner remains elusive. Here, we quantify the overlap of genes identified through large-scale 4 genome-wide association studies (GWAS) for 62 complex traits and diseases with genes known 5 to cause 20 broad categories of Mendelian disorders. We identify a significant enrichment of 6 phenotypically-matched Mendelian disorder g… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 105 publications
6
49
2
Order By: Relevance
“…In these cases, mechanistic inference depends on connecting association signals to their downstream targets (see below). For many traits, there is clear convergence between common-variant association signals and genes implicated in monogenic forms of the same disease, as well as enrichment of GWAS signals in regulatory elements specifically active in cell types consistent with known disease biology 60,61 . This provides reassurance that, even as the number of association signals for a given disease proliferates, the genetic associations uncovered will coalesce around molecular and cellular processes with a core role in pathogenesis 62,63 .…”
Section: Reviewmentioning
confidence: 99%
“…In these cases, mechanistic inference depends on connecting association signals to their downstream targets (see below). For many traits, there is clear convergence between common-variant association signals and genes implicated in monogenic forms of the same disease, as well as enrichment of GWAS signals in regulatory elements specifically active in cell types consistent with known disease biology 60,61 . This provides reassurance that, even as the number of association signals for a given disease proliferates, the genetic associations uncovered will coalesce around molecular and cellular processes with a core role in pathogenesis 62,63 .…”
Section: Reviewmentioning
confidence: 99%
“…First, the transition to WGS as a universal technology will detect variants regardless of location and frequency, making the codingnoncoding and rare-common distinctions unnecessary from a technical perspective. Furthermore, several studies have demonstrated a more complex, mixed genetic architecture of both common and rare disease even though optimal study designs for traits of different genetic architectures remain a matter of debate (Castel et al, 2018;Freund et al, 2018;Niemi et al, 2018;Weiner et al, 2017). Finally, a more refined understanding of functional effects of genetic variants challenges the simple coding-noncoding classification that often carries implicit assumptions that coding variants cause gene knockouts or disrupt protein structure, whereas noncoding variants fine-tune transcription levels.…”
Section: Functional Annotation and Prediction Of Genetic Variant Effectsmentioning
confidence: 99%
“…At SLC16A9, the observed association with gout was restricted to the lower Polynesian ancestry group (rs12356193, P � 0.006) [11]. Of note, the relationship between GWAS signals and genes underlying Mendelian phenotypes has been observed [47,48].…”
Section: Discussionmentioning
confidence: 94%